Principles of data management facilitating information sharing - Gordon, Keith (IT Pro., 2007)
Organisations increasingly view data as a valuable corporate asset and its effective management can be vital to success. This professional guide covers all the key areas including database development, data quality and corporate data modelling. It provides the knowledge and techniques required to successfully implement the data management function.